L2 Learners' Assessments of Accentedness, Fluency, and Comprehensibility of Native and Nonnative German Speech. Issue 4 (15th October 2014) - O'Brien, Mary Grantham
<x xml:space="preserve">Abstract</x> In early stages of classroom language learning, many adult second language (L2) learners communicate primarily with one another, yet we know little about which speech stream characteristics learners tune into or the extent to which they understand this lingua franca communication. In the current study, 25 native English speakers learning German as a L2 with varying levels of German proficiency rated German speech produced by native speakers and fellow learners of German along three continua: accentedness, fluency, and comprehensibility. An examination of speech stream (i.e., phonological, fluency based, and lexical/grammatical) characteristics along with partial correlations indicates both that the raters distinguished among the three concepts but that they conflated the term fluency with proficiency. Self‐reported proficiency in German and linguistic training were the best predictors of the ratings assigned.